PENINGKATAN KETAHANAN PANGAN KELUARGA MELALUI MODIFIKASI SEMPOL TAHU WORTEL (SEMPOTEL) DI DESA AIR ASAM - Chessy Sripratiwi; Summayya Salsabilla Putri; Amanda Dewi Pricilia; Aqilah Najiani Afifah; Aulia Rahma; Clarissa Naurah Salsabillah; Disky Oktariani; Helen Novita; Fetri Vera Girsang; Rahmat Fauzan; Siti Khoirunnisa; Siti Nur Humairah; Syahirah Rizki Anila (PARIPALAKA SRIWIJAYA, 2025)
Family food security is one of the determining factors for quality of life, especially for people in rural areas. The “Locally Nutritious for Us (LOKALITA)” program in Air Asam Village was implemented as an effort to improve the knowledge and skills of housewives in processing local food ingredients into healthy snacks through the creation of "Sempotel" (carrot tofu sempol). This activity involved 20 participants and included a series of activities in the form of filling out a pre-test, counseling on stunting and the benefits of local food ingredients, Sempotel making practice, product trials, and post-tests. The evaluation of the results showed a significant increase in knowledge in all indicators measured. Sempotel has been proven to have good nutritional value in one serving (3 pieces), namely 268.8 kilocalories of energy, 6.6 grams of protein, 16 grams of fat, and 25.8 grams of carbohydrates, so it is worthy of being categorized as an alternative healthy snack. The use of educational methods based on direct practice has been proven to be able to increase public awareness in utilizing local food potential optimally. This innovation is expected to support the realization of sustainable family food security in the future.